Regulation of secondary growth by poplar BLADE-ON-PETIOLE genes in Arabidopsis - Li, Sibei; Devi, Bhaswati; Allam, Gamalat; Bhullar, Armaan; Murmu, Jhadeswar; Li, Eryang; Hepworth, Shelley R. (Frontiers in Plant Science, 2023)
BLADE-ON-PETIOLE (BOP) genes are essential regulators of vegetative and reproductive development in land plants. First characterized in Arabidopsis thaliana (Arabidopsis), members of this clade function as transcriptional co-activators by recruiting TGACG-motif binding (TGA) basic leucine zipper (bZIP) transcription factors. Highly expressed at organ boundaries, these genes are also expressed in vascular tissue and contribute to lignin biosynthesis during secondary growth. Here, we investigate the functional conservation of Populus trichocarpa (poplar) orthologs of Arabidopsis BOP1 and BOP2, focusing on secondary growth, an important feature of wood development in trees. Within the poplar genome, two BOP-like genes were identified, PtrBPL1 and PtrBPL2, whose transcripts are abundant in stems. When heterologously expressed in Arabidopsis, promoter fusions to a β-glucuronidase (GUS) reporter gene were active in organ boundaries and in secondary xylem and phloem. We show that PtrBPL1 and PtrBPL2 complement leaf and flower patterning defects in Arabidopsis bop1 bop2 mutants. Furthermore, Arabidopsis plants overexpressing PtrBPL1 and PtrBPL2 show defects in stem elongation and the lignification of secondary tissues in the hypocotyl and stem. Finally, PtrBPL1 and PtrBPL2 formed complexes with TGA bZIP proteins in yeast. Our findings collectively suggest that PtrBPL1 and PtrBPL2 are orthologs of Arabidopsis BOP1 and BOP2 that may contribute to secondary growth regulation in poplar trees.